UNDERSTANDING YOUTH MENTAL HEALTH: A CRITICAL EXAMINATION OF PERSONALITY DISORDERS IN JENNIFER NIVEN'S ALL THE BRIGHT PLACES - Ali, Muhammad Ilham; Katili, Yayu Anggrani H.; Simanjuntak, Rutmintauli (Department of English Education, Universitas Panca Sakti Bekasi, 2024)
This study examines the manifestation of personality disorders through the character of Theodore Finch in the film adaptation of